Comparative physico-chemical stability of Fe-based powders with various phase compositions and dispersions in inorganic and biological media of alive organism - Boshyts’ka, N.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
A comparative investigation of the interaction of iron-based powders of various phase compositions with model biological media in an in vitro experiment has been performed. Pure coarse and fine α-Fe powders, and powders of the phase compositions (mass %) 93α-Fe+7Fe3O4 and 20α-Fe+80Fe3O4, have been investigated. As a biological medium, blood plasma was used, and, as inorganic media, distilled water (pH 7.0), a 0.01 N aqueous solution of hydrochloric acid (pH 2.0), and aqueous solution of sodium hydroxide (pH 7.4) were chosen. The obtained data indicate that an increase in the content of the α-Fe phase in the two-phase powders, which combines readily with blood proteins (ferritin and transferrin) increases the intensity of their interaction with the media containing blood plasma. In coarse PZhRV 3.200.26 iron powder and carbonyl iron powder, corrosion processes with the formation of hydrate forms of iron oxides dominate. On the basis of experimental data, it has been concluded that Fe3O4 powders are stable as compared with α-iron powders both in aqueous media and in media containing blood plasma. Thus, changing the technological conditions of synthesis of iron-based powders, one can obtain powders with a complex of physico-chemical characteristics (phase composition, high specific surface area, chemical stability in blood plasma and tissue fluid) that are necessary for using them for medical purposes.